Wide-Band High-Gain DGS Antenna System for Indoor Robot Positioning. (20th January 2019) - Bai, Lu; Du, Chenglie
Abstract : Based on multisource wireless signal fusion technology, the autonomous positioning systems of robots have been widely employed. How to design a compact compostable antenna array for indoor robot positioning is still a problem. In this study, we proposed a compact ultrathin antenna unit that effectively reduces the mutual coupling between any adjacent units, while covering most of the existing communication bands, including 2G/3G/4G/Wi-Fi, which will greatly reduce the size of the positioning antenna array. The proposed antenna system has been employed for positioning purpose with high-gain, wide-frequency band and limited size. It necessarily improves the accuracy of positioning signal from various unknown sources and finally accomplishes its autonomous positioning function.